Aging Induces Changes in the Somatic Nerve and Postsynaptic Component without Any Alterations in Skeletal Muscles Morphology and Capacity to Carry Load of Wistar Rats - Neto, Walter Krause (2017)
The present study aimed to analyze the morphology of the peripheral nerve, postsynaptic compartment, skeletal muscles and weight-bearing capacity of Wistar rats at specific ages. Twenty rats were divided into groups: 10 months-old (ADULT) and 24 months-old (OLD). After euthanasia, we prepared and analyzed the tibial nerve using transmission electron microscopy and the soleus and plantaris muscles for cytofluorescence and histochemistry. For the comparison of the results between groups we used dependent and independent Student's t-test with level of significance set at p <= 0.05. For the tibial nerve, the OLD group presented the following alterations compared to the ADULT group: larger area and diameter of both myelinated fibers and axons, smaller area occupied by myelinated and unmyelinated axons, lower numerical density of myelinated fibers, and fewer myelinated fibers with normal morphology. Both aged soleus and plantaris end-plate showed greater total perimeter, stained perimeter, total area and stained area compared to ADULT group (p < 0.05). Yet, aged soleus end-plate presented greater dispersion than ADULT samples (p < 0.05). For the morphology of soleus and plantaris muscles, density of the interstitial volume was greater in the OLD group (p < 0.05). No statistical difference was found between groups in the weight-bearing tests. The results of the present study demonstrated that the aging process induces changes in the peripheral nerve and postsynaptic compartment without any change in skeletal muscles and ability to carry load in Wistar rats.